2021
DOI: 10.1177/03331024211046617
|View full text |Cite
|
Sign up to set email alerts
|

Migraine evolution after the cessation of CGRP(-receptor) antibody prophylaxis: a prospective, longitudinal cohort study

Abstract: Background National and international guidelines recommend stopping migraine prophylaxis with CGRP(-receptor) monoclonal antibodies after 6–12 months of successful therapy. In this study, we aimed to analyze the course of migraine for four months after the cessation of CGRP(-receptor) antibodies use. Methods This longitudinal cohort study included patients with migraine who received a CGRP-(receptor) antibody for ≥8 months before treatment cessation. We analyzed headache data in the four-week period prior to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 34 publications
4
58
1
6
Order By: Relevance
“…More recently, Raffaelli et al [ 16 ] confirmed that the cessation of mAbs targeting the CGRP pathway determines an increase in migraine frequency and acute medication intake in patients treated with mAbs targeting CGRP receptor (erenumab) or ligand (fremanezumab and galcanezumab). Moreover, the authors observed a faster MMDs increase in patients treated with the former than with the latter, probably related to the shorter elimination half-life of erenumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Raffaelli et al [ 16 ] confirmed that the cessation of mAbs targeting the CGRP pathway determines an increase in migraine frequency and acute medication intake in patients treated with mAbs targeting CGRP receptor (erenumab) or ligand (fremanezumab and galcanezumab). Moreover, the authors observed a faster MMDs increase in patients treated with the former than with the latter, probably related to the shorter elimination half-life of erenumab.…”
Section: Discussionmentioning
confidence: 99%
“…This is a priori analysis. The sample size was considered in line with previous studies on the topic [ 16 20 ]. To achieve a power of 80% and a level of significance of 5% (two-sided), for detecting an effect size of 0.25 between paired variables, we calculated a sample size of at least 128 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…have not yet been identified. Real-world studies, which allow the evaluation of patients generally excluded from most clinical trials (e.g., with several drug class failures), have mainly been focused on erenumab, the first anti-CGRP mAb to receive approval, following varying discontinuation periods from 1 to 4 months [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent real-world studies describe a worsening of migraine after the discontinuation of CGRP(−R) mAbs [ 19 , 20 ]. We reported a significant increase in monthly migraine days (MMD) already one month after the discontinuation of CGRP(−R) mAb therapy with a return to baseline levels after three months [ 21 ]. To date, no real-world data about health-related quality of life (HRQoL) after the cessation of mAb therapy exists.…”
Section: Introductionmentioning
confidence: 99%